2019
DOI: 10.3389/fimmu.2019.01820
|View full text |Cite
|
Sign up to set email alerts
|

IgM Antibodies Can Access Cryptic Antigens Denied to IgG: Hypothesis on Novel Binding Mechanism

Abstract: Antibodies are well-known protein mediators of immunity. IgM is the primordial member and the neglected sibling of the later-evolved and more proficient IgG in regard to their therapeutic and diagnostic use. Serendipitously, however, we found a paradox: While murine IgM antibodies specific for guanosine triphosphate (GTP) were able to recognize native guanylyl antigens found in primate or rat muscle tissues by immunofluorescence assays (which mimicked the auto-antibodies from autoimmune patients to skeletal or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…By day 21 post-transfusion, the type of deposited immunoglobulin gradually switched from primarily IgM to IgG. In addition to the engagement of specific antibodies, deposition of complement C3 was detected on day 5 posttransfusion and the fixation of complement C3 on the surface of JMH-positive RBCs, then gradually decreased over time, which might be related to the transformation from IgM to IgG in the later stage [75,76]. The most obvious example of this phenomenon is that only one IgM antibody can initiate the deposition of complement through C1q, while two IgG molecules initiate the deposition of complement [56,77,78].…”
Section: Discussionmentioning
confidence: 93%
“…By day 21 post-transfusion, the type of deposited immunoglobulin gradually switched from primarily IgM to IgG. In addition to the engagement of specific antibodies, deposition of complement C3 was detected on day 5 posttransfusion and the fixation of complement C3 on the surface of JMH-positive RBCs, then gradually decreased over time, which might be related to the transformation from IgM to IgG in the later stage [75,76]. The most obvious example of this phenomenon is that only one IgM antibody can initiate the deposition of complement through C1q, while two IgG molecules initiate the deposition of complement [56,77,78].…”
Section: Discussionmentioning
confidence: 93%
“…The reasons for the successful analysis of the pairing are as follows: (1) The IgM mAb 79A11 of the paired mAbs was derived from the spleen cells of an immunized mouse, and the IgG2a mAb of the paired mAb was also derived from the same immunized mouse lymph node cells, which confirmed that the two mAbs are directed against two different epitopes in the same antigen HPV16 E7-HIS fusion oncoprotein. (2) Although the affinity of IgG and an antigen is stronger than IgM, as a pentamer, an IgM can bind to 10 antigens and can access cryptic antigens denied to IgG [33]. IgM was used as a capture antibody in the double-antibody sandwich ELISA with less steric hindrance, which was more suitable for capturing antigens [34].…”
Section: Discussionmentioning
confidence: 99%
“…The high-risk human papillomavirus (HPV) integrating the cervix is a direct cause of cervical precancerous lesions and cervical cancer [1]. HPV 16 and 18 account for > 70% of cervical cancers and HPV 31,33,35,45,52, and 58 account for an additional 20% [2,3]. The prevalence of HPV infection in the cervix among women is 42.7% in the USA [4] and 17.7% in China [5].…”
Section: Introductionmentioning
confidence: 99%
“…This only required high-affinity surface binding, subsequently slowing down VSG surface recycling, leading to motility arrest and rapid cell death. As such, while IgGs might have a higher binding affinity as compared to IgMs, the latter have an improved binding avidity due to their decavalent binding pattern and unique epitope recognition [104]. While VSG-antibody interaction modeling shows that when one IgG 'VH/VL arm' binds to VSG one homodimer, the other 'arm' can bind to any of 18 other VSG homodimers on the parasite surface [105], this number is increased to 9 IgM 'arms' being able to bind any of 61 other VSG homodimers, tremendously increasing avidity [106].…”
Section: Plos Pathogensmentioning
confidence: 99%